Settling characteristics of nanoparticles in ethanol-water mixtures - ILYAS, SUHAIB UMER (2013)
Nanofluids are dilute suspensions of functionalized nanoparticles having diameter less than 100 nm. Settling of nanoparticles due to gravity is a natural phenomenon and the only predicament towards their usage in industrial scale. Knowledge of sedimentation behavior of nanoparticles is a topic of great interest as not much information is available on the settling characteristics of nanosuspensions in different combinations. Formation of agglomerates due to aggregation among particles in a nanosuspension promotes the sedimentation process. Agglomeration takes place when randomly moving particles come closer in a base liquid and join together due to strong attractive forces to form particle clusters.